Biomechanical Analysis of Discus Throwing at the 1996 Atlanta Olympic Games - Ariel, G.; Penny, A.; Finch, A.
The throwing velocities determined were similar to the velocities calculated for in analyses performed by Ariel in 1976 ? on Silvester and Oerter. There were negligible differences in the projection angles used by the 4 best discus throwers in the Atlanta Olympics but there were significant differences in the resultant projection velocities between the top 4 contestants analyzed. Riedel, the gold medalist generated the greatest projection velocity of 3170.1 cm/sec and Washington had a projection velocity of 2484.9 cm/sec, which represented an 28% increase in solely the speed of the discus over the fourth place finisher. Interestingly enough, Washington performed the throwing movement in 46% less time, while Riedel took the longest amount of time to release the discus. This may indicate that Washington moved across the circle too quickly, thus not allowing enough time for the storage of elastic energy in the arm during the turns and then consequently a lower energy return was observed at the release of the discus. The study successfully demonstrated that digitization is a biomechanical task which can be performed between different geographical locations using the Internet as the interfacing medium. The applications of this technique and intellectual resource appear unlimited. For example, a golf teacher in New York can video his students' swings. These video clips can be transmitted digitally in AVI format to a server in one part of the world and then interfaced to the biomechanical program for further analysis. Many Olympic events make fixed laboratory studies difficult, including equine events, sailing, and cross-country skiing. Coaches can film actual performances on site using cameras with direct AVI format input attached to Laptop computers. These files can then be digitized or transmitted through Internet protocols. Biomechanical quantification has developed far beyond the pioneers who relied upon visual observations of animation to describe movement. The revolution continued with improvements in cameras, the introduction of computers, development of various algorithms to better fit the data, and expansion beyond sports studies. Additional innovations in the process are expected as the Internet further evolves into newer presentation technologies involving animation and virtual reality (e.g. Java and VRML). The ability to quantify motion has appeal to many groups and at many different levels. Access to global resources via the Internet expands biomechanics beyond a fixed geographical location. This has direct applications in medical research and industrial engineering where, frequently, transmission and processing of research data between remote sites has to occur in a real-time mode. Thus, the subject presented and studied in this document represents a significant threshold in furthering the accessibility and applicability of Biomechanics to several scientific, medical, industrial and aeronautical endeavors far beyond its present reach.